“The Voice of the Universe”: Cosmic Immanence in John Elof Boodin’s Process Thought, What It Is and Why It Matters - Flannery, Michael A. 1953- (2024)
For most, the way to process thought has been through mathematician-turned-philosopher Alfred North Whitehead (1861–1947). However, his contemporary, Swedish–American philosopher John Elof Boodin (1869–1950), offers another path. While both clearly exposit a process-based philosophy/theology, there are important differences. The main purpose of this essay is to delineate those differences and highlight Boodin’s concept of cosmic immanence (CI) as a key feature separating him from Whitehead’s metaphysic. It is argued that CI can provide the heavy lifting for developing a coherent and satisfying process theology without the baggage attached to Whitehead’s difficult intricate interconnections and enigmatic neologisms. In other words, Boodin’s criticisms of Whitehead (of which there were several) do not amount to an abandonment of process-based thinking or even Whitehead’s larger project of developing a coherent process theology. However, the addition of a new synthesis—merging Boodin’s CI with Joseph A. Bracken’s trinitarian God/world thesis and Ludwig von Bertalanffy’s general systems theory (GST)—is necessary for completion. This new CI synthesis suggests that the same process-based destination can be arrived at by an easier and clearer route.
Keywords: Alfred North Whitehead; Process theology; Metaphysics; general systems theory; cosmic immanence; John Elof Boodin